Pemulihan Dalam Hosea 2 Bagi Pasangan Yang Mengalami Krisis Ketidakpastian - Sigit Ani Saputro; Mefiani Wau (Sekolah Tinggi Teologi Berita Hidup, 2026)
This study aims to provide an exegetical interpretation of Hosea 2 to explore patterns of relational restoration that can be applied in the context of Christian marriages facing a crisis of infidelity. It employs a historical-grammatical method by analyzing the historical context, literary structure, and the meaning of key words and phrases in the Hebrew text. The findings indicate that Hosea 2 contains five principles of relational restoration: steadfast love amidst betrayal, active steps to prevent further damage, honest emotional communication, a willingness to accept one’s partner fully, and a commitment to continuously rebuild the relationship. These five principles demonstrate a holistic pattern of restoration, beginning with rebuke and culminating in a renewed commitment to the relationship. Thus, this study offers a biblical-theological framework that can serve as a foundation for pastoral counseling in addressing crises of infidelity within Christian marriages. Krisis keluarga pada masa modern, baik yang disebabkan oleh tekanan ekonomi, perilaku maupun perubahan zaman, telah memperlemah ketahanan kesetiaan dalam hubungan suami istri. Hosea pasal 2 menggambarkan situasi krisis serupa melalui relasi Hosea dan Gomer, sekaligus menunjukkan bagaimana pemulihan dapat terjadi meskipun hubungan telah rusak karena ketidaksetiaan. Penelitian ini menggunakan metode tafsir historis-biblika dengan pendekatan kontekstual untuk menyingkap makna pemulihan yang terkandung dalam Hosea 2. dari hasil kajian ditemukan beberapa prinsip pemulihan, yaitu kasih yang aktif, kejujuran dalam komunikasi, kesiapan menerima pasangan, keterbukaan dalam keuangan, dan komitmen sejati. kasih yang menuntun pada pertobatan dan memulihkan hubungan yang telah retah Kata Kunci: Hosea 2, pemulihan, ketidaksetiaan, keluarga Kristen, kasih sejati.